Neurocognitive deficits in children and adolescents following maltreatment: Neurodevelopmental consequences and neuropsychological implications of traumatic stress. Issue 1 (2nd January 2017) - Kavanaugh, Brian C.; Dupont-Frechette, Jennifer A.; Jerskey, Beth A.; Holler, Karen A.
ABSTRACT: Childhood maltreatment is a significant risk factor for a host of psychiatric, developmental, medical, and neurocognitive conditions, often resulting in debilitating and long-term consequences. However, there is no available neuropsychological resource reviewing the literature on the associated neurocognitive deficits in children and adolescents. This review comprehensively examines the 23 prior studies that evaluated the intellectual, language, visual-spatial, memory, motor, and/or attention/executive functions in children and adolescents following an experience of childhood abuse and/or neglect. Neurocognitive impairments were frequently reported. Impairments in executive functions were the most frequent and severe reported impairments, although intelligence, language, visual-spatial skills, and memory are also at serious risk for compromised development following maltreatment. However, specific factors such as abuse/neglect duration, severity, type, and timing during development were all associated with neurocognition. This indicates that these factors are of greater importance than just the presence of abuse/neglect in identifying risk for neurocognitive compromise. Such neurocognitive deficits appear to be a consequence to the known neurobiological and brain development abnormalities of this population, suggesting traumatic stress can be a potential cause of neurodevelopmental disorders. These findings have critical implications for the clinical practice and research involving children following childhood maltreatment and other types of traumatic stress.